Comparison of Changes in Quality of Life Based on Changes in Disease Severity in Graves Ophthalmopathy Patients Following Intraorbital Triamcinolone Acetonide Injection: Oral Presentation - Observational Study - Resident - LADY PRANODIA SUKMAWIDOWATI (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Graves ophthalmopathy (GO) is associated with visual impairment and appearance changes, affecting the quality of life. Intraorbital injection of triamcinolone acetonide (TCA) in GO resulted in clinical improvement, but its effect on the quality of life is unknown. The objective of this study was to compare the changes in quality of life after intraorbital injection of TCA between different groups based on changes in disease severity. Methods : Intraorbital injection of TCA was performed on 30 subjects with GO. Disease severity was assessed according to the European Group of Graves Ophthalmopathy (EUGOGO) criteria. Quality of life was measured using the Indonesian version of Graves Ophthalmopathy Quality of Life (GO-QOL) questionnaire. Changes in disease severity and GO-QOL scores were recorded before intraorbital injection of TCA and 1 month after. Subjects were divided into groups based on changes in disease severity: decreased, remained constant, and increased. Changes in quality of life between the groups were compared statistically. Results : Changes in GO-QOL appearance scores in patients with decreased disease severity were significantly higher (p= 0.016) than those in patients whose disease severity remained constant. Changes in GO-QOL visual function scores in patients with decreased disease severity were higher but not statistically significant (p> 0.05) compared to those in patients whose disease severity remained constant. Conclusion : Changes in the appearance aspect of quality of life after intraorbital injection of TCA in patients with decreased disease severity are better than that in patients whose disease severity remained constant, whereas changes in the visual function aspect are not significantly different.